Halogen-bond-based cooperative ion-pair recognition by a crown-ether-embedded 5-iodo-1, 2, 3-triazole. Issue 14 (2nd February 2017) - Tepper, Ronny; Schulze, Benjamin; Bellstedt, Peter; Heidler, Jan; Görls, Helmar; Jäger, Michael; Schubert, Ulrich S.
Abstract : A heteroditopic receptor with an iodo-triazole moiety for simultaneous cation–anion binding through Lewis-basic nitrogen atoms and halogen-bond-donating iodine atoms was designed. Abstract : A crown-ether containing the iodo-triazole moiety for simultaneous cation–anion binding through Lewis-basic nitrogen atoms and C–I⋯I halogen-bond-donating iodine atoms was prepared. The complexation of the heteroditopic receptor was illustrated by X-ray and DFT analysis. The cooperative effect boosting the anion affinity was quantified by 1 H/ 13 C NMR titration experiments.